(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2018)
Addition operation is one of the material for students at Elementary School. One of those games that can help students in the operation of addition is congklak. Congklak is the Indonesian traditional games, through congklak’s game students can be more motivated. After making the game, students were asked to write down the results in the prepared sheet. Then, their sheets can be showed by their friend. The impact of this learning is the learning atmosphere becomes more exciting and the students do not get bored in the class. Writer hope that this game can be improved student’s skill to addition operation.